1990
DOI: 10.1046/j.1537-2995.1990.30690333480.x
|View full text |Cite
|
Sign up to set email alerts
|

Platelet transfusions administered to patients with splenomegaly

Abstract: It is generally felt that increments in platelet counts following platelet transfusions to patients with splenomegaly are severely reduced as a result of splenic sequestration. The results of 631 random-donor platelet transfusions administered to 66 thrombocytopenic patients with palpable splenomegaly were analyzed. Increasing splenomegaly had a significant effect on corrected count increments (CCIs), with the greatest deterioration occurring in patients whose spleens were palpable greater than 2.0 cm below th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…A transfusion was considered successful when the 1 h post-transfusion platelet recovery was > 20%. At the time of each transfusion the presence or absence of the following conditions that might reduce platelet survival were documented: temperature, septicaemia, splenomegaly, disseminated intravascular coagulation, and major haemorrhage (a decrease of haemoglobin value of 2 mmol/l or more within 24 h) (Bishop et al, 1988(Bishop et al, , 1991McFarland et al, 1989;Hussein et al, 1990;Friedberg et al, 1993;Doughty et al, 1994).…”
Section: Methodsmentioning
confidence: 99%
“…A transfusion was considered successful when the 1 h post-transfusion platelet recovery was > 20%. At the time of each transfusion the presence or absence of the following conditions that might reduce platelet survival were documented: temperature, septicaemia, splenomegaly, disseminated intravascular coagulation, and major haemorrhage (a decrease of haemoglobin value of 2 mmol/l or more within 24 h) (Bishop et al, 1988(Bishop et al, , 1991McFarland et al, 1989;Hussein et al, 1990;Friedberg et al, 1993;Doughty et al, 1994).…”
Section: Methodsmentioning
confidence: 99%
“…This study provides evidence that immune mechanisms were not the predominant cause of platelet refractoriness in the patient population studied. It also suggests that measures for the prevention of HLA alloimmunisation, such as leucocyte depletion, may have a limited impact in reducing the in cidence of refractoriness to platelet transfusions.bleeding [10][11][12], disseminated intravascular coagulation (DIC) [13,14], and splenomegaly [12,[15][16][17], A multiple linear regression analysis identified the major factors as sociated with refractoriness as splenomegaly, administra tion of amphotericin B, bone marrow transplantation, HLA antibodies and DIC [18].Previous studies have shown that HLA alloimmunisa tion and platelet refractoriness are reduced by the use of leucocyte-depleted blood components [19][20][21][22][23][24][25], However, doubt remains about the cost-effectiveness of leucocyte depletion of blood components for the prevention of pla telet refractoriness [26]. Although leucocyte depletion might prevent refractoriness due to HLA alloimmunisa-…”
mentioning
confidence: 99%
“…Splenomegaly has been identified as a cause of platelet refractoriness in many studies (Parker et al, 1974;Bishop et al, 1988;Hussein et al, 1990). In our series there were few patients with splenomegaly, which may account for the lack of statistical significance in the multivariate analysis.…”
Section: Discussionmentioning
confidence: 60%